2021
DOI: 10.3389/fped.2021.787353
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Between Multisystem Inflammatory Syndrome, Associated With COVID-19 in Children and the Kawasaki Disease: Development of Preliminary Criteria Based on the Data of the Retrospective Multicenter Cohort Study

Abstract: Objectives: Diagnostic between multisystem inflammatory syndrome associated with COVID-19 in children (MIS-C) and Kawasaki disease (KD) can make difficulties due to many similarities. Our study aimed to create a Kawasaki/MIS-C differentiation score (KMDscore) allowing discrimination of MIS-C and KD.Study design: The retrospective multicenter cohort study included clinical, laboratory, and instrumental information about MIS-C (n = 72) and KD (n = 147). The variables allowed to discriminate both conditions used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 37 publications
10
29
1
1
Order By: Relevance
“…Lymphopenia and thrombocytopenia have been reported in the literature to accompany MIS-C cases, as seen in our study, whereas leukocytosis was observed in Kawasaki patients. In addition, sedimentation, CRP, ferritin, and D-dimer levels were also higher as acutephase reactants in patients with MIS-C in previous studies [4,19,28]. However, no significant difference was found between the two groups in our study from the standpoint of acute-phase reactants.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Lymphopenia and thrombocytopenia have been reported in the literature to accompany MIS-C cases, as seen in our study, whereas leukocytosis was observed in Kawasaki patients. In addition, sedimentation, CRP, ferritin, and D-dimer levels were also higher as acutephase reactants in patients with MIS-C in previous studies [4,19,28]. However, no significant difference was found between the two groups in our study from the standpoint of acute-phase reactants.…”
Section: Discussioncontrasting
confidence: 65%
“…According to this study, the duration of fever before diagnosis was shorter in MIS-C, which is consistent with other studies. Furthermore, in other studies, the fever resolved in a shorter period [19]. One of the most important factors affecting this result is thought to be the difference in diagnostic criteria.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A strength of our work is the universal availability of the required features in the majority of healthcare settings and the validation using external cohorts. The only published model addressing a machine learning approach to MIS-C diagnosis includes features that may not be available in many clinical settings such as ferritin and D-dimer 15 . In addition, the model was not tested against febrile pediatric control patients and was not externally validated.…”
Section: Discussionmentioning
confidence: 99%
“…Children with MIS-C are often older than 5 years of age ( 18 ). Laboratory tests might show thrombocytopenia, the elevation of CRP, ferritin, troponin, and D-dimer in patients with MIS-C ( 25 , 26 ). Our case showed symptoms of fever, skin rash, conjunctival injection, and periungual peeling of skin in the fingers and toes, which could be found in KD and MIS-C.…”
Section: Discussionmentioning
confidence: 99%